THE CONTRASTIVE ANALYSIS OF ENGLISH AND AMBONESE PERSONAL PRONOUN - Dewi Qhuril Malasari Ely; Nana Ronawan Rambe (LP2M UIN Abdul Muthalib Sangadji Ambon, 2023)
The purpose of this study is to find out the difference and similarity of the English and the Ambonese personal pronouns based on those standard grammatical literary sources. Type of research descriptive qualitative research. The data were collected using observation, interview and recording of native speaker speech. The finding showed that the form of personal pronouns in English and Ambonese languages have variation based on gender. In English, variations in the use of personal pronouns based on gender are found in the use of third singular person he and she. Whereas in Ambonese language, variations in the use of personal pronoun by gender are found in the use of second singular person, abang, caca, bu and usi. The differences between English and Ambonese in their function as subjective and objective pronoun are English personal pronoun is more varied than Ambonese personal pronoun because almost all of English personal pronoun is different according to the function except you and it. Unlike the English personal pronoun, all Ambonese personal pronouns are the same between subjective and objective pronoun. Ambonese personal pronoun is also based on considerations of gender, age and politeness distinction. The similarities between English and Ambonese personal pronoun is based on considerations of gender.